Women's experiences of VBAC in Cyprus: a qualitative study - Hadjigeorgiou, Eleni; Katsie, Constantina; Papadopoulou, Maria; Christofi, Maria Dolores; Christoforou, Andri (My University, 2021)
In 21st century, there has been an increasing interest in vaginal birth after previous caesarean section (VBAC) in Cyprus, a country with a very high operative birth rate. Research-based evidence of women's VBAC experiences in Cyprus is non-existent, despite its significance for the well-being of mothers and families. The aim of this study is to gain insight into the women's lived experience of VBAC in Cyprus. In this study women's experiences of VBAC are explored for the first time in Cyprus.
Keywords: VBAC; Vaginal birth after c-sections OR vaginal birth after caesarean section; Women’s experiences; Women’s perceptions; Women’s views